2012
DOI: 10.1371/journal.pone.0045225
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of IL-33R (ST2) Abrogates Resistance to EAE in BALB/C Mice by Enhancing Polarization of APC to Inflammatory Phenotype

Abstract: The administration of interleukin 33 and deletion of IL-33 receptor, ST2 molecule, affects the induction of autoimmunity in different experimental models of human autoimmune diseases. The aim of this study was to analyze the effect of ST2 deletion on the induction of experimental autoimmune encephalomyelitis (EAE) in resistant BALB/c mice. Mice were immunized with MOG35–55 peptide or disease was induced by passive transfer of encephalitogenic singenic cells and EAE was clinically and histologically evaluated. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
51
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 64 publications
(53 citation statements)
references
References 57 publications
1
51
0
1
Order By: Relevance
“…Although high expression of IL-33 mRNA in the brain and spinal cord of mice was also demonstrated (Schmitz et al, 2005), there are controversial studies regarding its role in the EAE (Milovanovic et al, 2012a). As mentioned above, the Th1 and Th17 cells were thought to be responsible for the inflammatory demyelination in MS and EAE (Mix et al, 2010;Buc, 2013), while Th2 and Treg cells have been shown to be important in the resolution stages of the disease (Tumani et al, 2011;Buc, 2013).…”
Section: Pbs-treated Eaementioning
confidence: 99%
See 1 more Smart Citation
“…Although high expression of IL-33 mRNA in the brain and spinal cord of mice was also demonstrated (Schmitz et al, 2005), there are controversial studies regarding its role in the EAE (Milovanovic et al, 2012a). As mentioned above, the Th1 and Th17 cells were thought to be responsible for the inflammatory demyelination in MS and EAE (Mix et al, 2010;Buc, 2013), while Th2 and Treg cells have been shown to be important in the resolution stages of the disease (Tumani et al, 2011;Buc, 2013).…”
Section: Pbs-treated Eaementioning
confidence: 99%
“…Accordingly it has been suggested that the IL-33 plays a therapeutic role in EAE by converting a pathogenic Th17/Th1 response to Th2 activity and/or by polarization of anti-inflammatory M2 macrophages (Jiang et al, 2012). It has also been demonstrated that the deletion of IL-33R (ST2) abrogates the inherent resistance of BALB/c mice to EAE induction by enhancing differentiation of proinflammatory antigen presenting cells and differentiation of encephalitogenic T cells (Milovanovic et al, 2012a). On the other hand, it has also been demonstrated that IL-33 drives Th1/Th17 responses in some experimental models of immune disorders (Milovanovic et al, 2012b).…”
Section: Pbs-treated Eaementioning
confidence: 99%
“…Modulation of immune responses has been suggested to exacerbate or attenuate EAE in susceptible strains of mice (51). Alternatively, our previous study recently showed that alteration of an immunoregulatory pathway by deleting components of the IL-33/ST2 axis may enhance susceptibility to EAE in the resistant BALB/c strain by inducing an inflammatory phenotype in antigen presenting cells (52,53). In accord with the significantly increased expansion of IL-10-producing peritoneal B1a cells in BALB/c mice compared with susceptible C57BL/6 mice and the fact that peritoneal B cells migrate to lymph nodes (54), it could be assumed that the increased number of peritoneal B1 cells could contribute to the regulatory phenotype of dendritic cells in draining lymph nodes and the resistance of BALB/c mice to the development of EAE.…”
Section: B1 Cells In Eaementioning
confidence: 99%
“…We have recently shown that the encephalitogenic antigens MOG or MBP induced peripheral tolerance in Balb/c mice following inoculation of the antigens via the AC (Farooq and Ashour, 2013) or after the intravenous injections of MOG 35-55 -specific/MBP-specific ACAID antigen presenting cells (APCs), MOG 35-55 -specific/MBP-specific ACAID B cells, and MOG 35-55 -specific/MBP-specific ACAID Tregs (Farooq and Ashour, 2014). It is noteworthy that EAE induction is possible in Balb/c mice after targeted disruption of ST2 molecule but is entirely possible in C57BL/6 mice (Milovanovic et al, 2012). Therefore, we aimed to investigate whether MOG 35-55 -specific/MBP-specific ACAID could be induced in C57BL/6 mice.…”
Section: Introductionmentioning
confidence: 99%